The Architecture of Cinematic Spaces : by Interiors - Ahi, Mehruss Jon; Karaoghlanian, Armen (Intellect Books, 2020)
The Architecture of Cinematic Spaces by Interiors is an academic, graphic exploration of architectural spaces in cinema that provides a new perspective on the relationship between architecture and film. Combining critical essays with original architectural floor plan drawings, the book discusses production design in key films from the twentieth and twenty-first centuries, including The Cabinet of Dr. Caligari, Rope, Le mépris, Playtime, 2001: A Space Odyssey, Home Alone, Panic Room, A Single Man, Her and Columbus. Each chapter is accompanied by an original floor plan of a key scene, bridging the gap between film criticism and architectural practice. The book, written by the editors of the critically acclaimed online journal Interiors, will appeal to both film and architecture communities, and everyone in between. A must-read for fans and scholars alike, this volume prompts us to reconsider the spaces our favourite characters occupy and to listen to the stories those spaces can tell.